2023
DOI: 10.3724/abbs.2023155
|View full text |Cite
|
Sign up to set email alerts
|

PGAM5 deacetylation mediated by SIRT2 facilitates lipid metabolism and liver cancer proliferation

Abstract: Tumor metabolic reprogramming and epigenetic modification work together to promote tumorigenesis and development. Protein lysine acetylation, which affects a variety of biological functions of proteins, plays an important role under physiological and pathological conditions. Here, through immunoprecipitation and mass spectrum data, we show that phosphoglycerate mutase 5 (PGAM5) deacetylation enhances malic enzyme 1 (ME1) metabolic enzyme activity to promote lipid synthesis and proliferation of liver cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Malic enzyme 1 (ME1) is an NADP (+)-dependent enzyme that links glycolysis and the TCA cycle. Using immunoprecipitation and mass spectrum data, Fu and colleagues demonstrated that deacetylation of phosphoglycerate mutase 5 boosts the activity of the ME1, thereby stimulating lipid synthesis and the proliferation of liver cancer cells [ 164 ]. Metabolic rewiring of glycoxenogenic enzyme phosphoenolpyruvate carboxykinase 1 (PCK1) disrupts hexosamine synthesis pathway-mediated O-GlcNAcylation and induces cataplerosis in the TCA cycle [ 165 , 166 ].…”
Section: Interactions Between Epigenetic Modifications and Hcc Cell M...mentioning
confidence: 99%
“…Malic enzyme 1 (ME1) is an NADP (+)-dependent enzyme that links glycolysis and the TCA cycle. Using immunoprecipitation and mass spectrum data, Fu and colleagues demonstrated that deacetylation of phosphoglycerate mutase 5 boosts the activity of the ME1, thereby stimulating lipid synthesis and the proliferation of liver cancer cells [ 164 ]. Metabolic rewiring of glycoxenogenic enzyme phosphoenolpyruvate carboxykinase 1 (PCK1) disrupts hexosamine synthesis pathway-mediated O-GlcNAcylation and induces cataplerosis in the TCA cycle [ 165 , 166 ].…”
Section: Interactions Between Epigenetic Modifications and Hcc Cell M...mentioning
confidence: 99%
“…Additionally, Pgam5 interacts with several key proteins, such as Parkin and PINK1, which are integral to mitochondrial quality control mechanisms. Recent studies have reported that Pgam5 affects liver cancer proliferation [35] and participates into the hepatic inflammation [36]. Besides, non-alcoholic steatohepatitis is also under the control of Pgam5 in a high fat/high fructose diet-treated mouse model [29].…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin 2 (SIRT2), a NAD + -dependent deacetylase, predominantly resides in the cytoplasm but also exists in mitochondria and the nucleus 14 . Recent studies highlight its significant role in various liver diseases, including hepatocellular carcinoma 15 , alcoholic liver disease 16 , and non-alcoholic fatty liver disease17. Tang et al demonstrated that SIRT2 binds to liver kinase B1 (LKB1), deacetylating it at lysine 48, thereby enhancing LKB1 phosphorylation and the subsequent LKB1-AMPK signaling activation 18 .…”
Section: Introductionmentioning
confidence: 99%